2009
DOI: 10.1002/jcb.22229
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β‐1,4‐galactosyltransferase I in rat Schwann cells

Abstract: Glycosylation is one of the most important post-translational modifications. It is clear that the single step of beta-1,4-galactosylation is performed by a family of beta-1,4-galactosyltransferases (beta-1,4-GalTs), and that each member of this family may play a distinct role in different tissues and cells. In the present study, real-time PCR revealed that the beta-1,4-GalT I mRNA reached peaks at 2 weeks after sciatic nerve crush and 3 days after sciatic nerve transection. Combined in situ hybridization for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…And it was reported that Schwann cells regulated b-1,4-GalT-I expression after LPS stimulation via ERK, JNK, and P38 MAP kinase signal pathways (Yang et al 2009). Therefore, it was an important question whether LPS induced activation of ERK, p38, and JNK was related to b-1,4-GalT-I expression in rat primary astrocytes.…”
Section: Discussionmentioning
confidence: 97%
“…And it was reported that Schwann cells regulated b-1,4-GalT-I expression after LPS stimulation via ERK, JNK, and P38 MAP kinase signal pathways (Yang et al 2009). Therefore, it was an important question whether LPS induced activation of ERK, p38, and JNK was related to b-1,4-GalT-I expression in rat primary astrocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, different ABO blood types show different activities of glycosyltransferases. Glycosyltransferases were reported in significant repair and regeneration in nerve injury, via glycosylation of glycoproteins in Schwann cells [48, 49]. Moreover, glycosyltransferases are also involved in neuroinflammatory response [50].…”
Section: Discussionmentioning
confidence: 99%
“…In support of our proposal, AA induces Src activation [Navarro‐Tito et al, 2008], and we demonstrate that Src mediates ERK1/2 activation, whereas ERK1/2 activity mediates the increase of GalT I expression induced by AA in MDA‐MB‐231 cells. Furthermore, an overexpression of ERK1 promotes an increase of GalT I expression in PGLH7 human lung cancer cells [Zhu et al, 2005], whereas ERK activity mediates GalT I expression in rat Schwann cells [Yang et al, 2009].…”
Section: Discussionmentioning
confidence: 99%